Multifunctionality in Mediterranean landscapes–past and future (The New Dimensions of the European Landscapes, 2004)
During past decades many of the traditional multifunctional Mediterranean landscapes with their typical complexes of agro-, silvo- and pastoral components changed thoroughly. Nowadays only few of them are still vital. Their complex farming systems secure at the same time a multitude of other functions than just agricultural production, such as support for recreation, amenity, cultural identity, preservation of natural resources and environmental quality. Some of these unique, old Mediterranean landscapes are discussed. They cover a broad range from near-tonature high mountain landscapes and terraced small-scale submediterranean polyculture landscapes to dry Mediterranean agro-silvo-pastoral landscapes. All these are changing, either spontaneously due to changing socio-economic and cultural conditions, or as a result of conscious policies, with the Common Agricultural Policy as a main driver. Even measures created to support specific traditional land uses and their landscapes are often not successful as they focus on only a part of the system. These policies and measures will not hold the valuable traditional systems from collapsing and subsequent vanishing. Some other policy instruments, such as those in forestry, are not meant to support them, but to transform them in favour of new monofunctionality. New strategies and instruments ought to deal with these multifunctional landscapes in a more integrated way, if some of them are to be maintained or transformed into others with similar qualities.